Yellow fever virus modulates cytokine mRNA expression and induces activation of caspase 3/7 in the human hepatocarcinoma cell line HepG2 - Holanda, Gustavo Moraes (Springer Verlag, 2019)
Yellow fever virus (YFV) penetrates the skin through the bite of a vector mosquito and spreads to various organs, mainly the liver, where it causes lesions and induces necrosis and apoptosis. We evaluated the mRNA expression of various cytokines and the activation of caspases in HepG2 cells infected with YFV. We observed that interferon-? (IFN-?) expression decreased and IFN-?, transforming growth factor (TGF)-? IIIR, interleukin (IL)-6, and IL-8 expression increased in cells infected with genotype 1. In contrast, TNF-? expression increased in cells infected with genotype 2 but not with genotype 1. This provides insights into the role of cytokine regulation in yellow fever.